Mastering XHTML (Sybex, 2002)
Provides users with comprehensive coverage of XHTML, the bridge between HTML and XML. --Includes a handy guide to XHTML tags, JavaScript, XHTML special characters, and color codes. --For intermediate to advanced-level XHTML coders, Mastering XHTML Premium Edition includes productivity tips and real-world XHTML projects, plus a CD loaded with productivity-enhancing software.